2020
DOI: 10.1111/andr.12950
|View full text |Cite
|
Sign up to set email alerts
|

Testicular steroid sulfatase overexpression is associated with Leydig cell dysfunction in primary spermatogenic failure

Abstract: Background Decreased testosterone (T) to LH ratio and increased 17β‐estradiol (E2) serum concentrations represent a common finding among patients with severe spermatogenic failure, suggesting a concurrent Leydig cell steroidogenic dysfunction. Aromatase overexpression has been associated with increased serum and intratesticular E2 in these patients. However, it is unknown whether the sulfatase pathway contributes to the increased availability of active estrogens in patients with primary spermatogenic failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Figure 5 presents a schematic illustration of es synthesis in testes. A recent study examining the quantity of estrogen sulfotransferase and steroid sulfatase mRNA in testicular tissue from SCOS patients found that an unbalanced steroid sulfatase/estrogen sulfotransferase pathway contributes to the testicular hyperestrogenic milieu in individuals with spermatogenic failure and LC dysfunction [280]. Moreover, decreased androgen production in SCOS was associated with lower CYP17A1 expression, which is affected by E2.…”
Section: Endocrine Profilementioning
confidence: 99%
“…Figure 5 presents a schematic illustration of es synthesis in testes. A recent study examining the quantity of estrogen sulfotransferase and steroid sulfatase mRNA in testicular tissue from SCOS patients found that an unbalanced steroid sulfatase/estrogen sulfotransferase pathway contributes to the testicular hyperestrogenic milieu in individuals with spermatogenic failure and LC dysfunction [280]. Moreover, decreased androgen production in SCOS was associated with lower CYP17A1 expression, which is affected by E2.…”
Section: Endocrine Profilementioning
confidence: 99%